2013
DOI: 10.1371/journal.pone.0061733
|View full text |Cite|
|
Sign up to set email alerts
|

Partial Agonism of Taurine at Gamma-Containing Native and Recombinant GABAA Receptors

Abstract: Taurine is a semi-essential sulfonic acid found at high concentrations in plasma and mammalian tissues which regulates osmolarity, ion channel activity and glucose homeostasis. The structural requirements of GABAA-receptors (GABAAR) gated by taurine are not yet known. We determined taurine potency and efficacy relative to GABA at different types of recombinant GABAAR occurring in central histaminergic neurons of the mouse hypothalamic tuberomamillary nucleus (TMN) which controls arousal. At binary α1/2β1/3 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…GABA A R lacking γ‐subunits are blocked by ZnCl 2 10 μM, whereas γ‐subunit‐containing receptors are weakly or not affected by this concentration (Draguhn et al ., ; Herb et al ., ). In contrast to the rat TMN neurons which are all zinc resistant (Sergeeva et al ., ), we found that, in about 30% of the mouse TMN neurons identified by the expression of HDC, GABA‐responses are about halved by ZnCl 2 10 μM (Kletke et al ., ). In the present study, pyrazolopyridine CGS 20625, a two to six times more potent positive modulator of α1β2 than of α1β2γ receptors (Khom et al ., ), confirmed γ‐subunit‐deficiency of zinc‐sensitive TMN neurons [CGS 20625's EC 50 = 1.1 ± 0.1 μM ( n = 5, 28% of total cell number], which is significantly different ( P = 0.0055) from the zinc‐resistant cells (EC 50 = 3.4 ± 0.4 μM, n = 13, Supporting Information http://onlinelibrary.wiley.com/doi/10.1111/bph.12280/suppinfo).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…GABA A R lacking γ‐subunits are blocked by ZnCl 2 10 μM, whereas γ‐subunit‐containing receptors are weakly or not affected by this concentration (Draguhn et al ., ; Herb et al ., ). In contrast to the rat TMN neurons which are all zinc resistant (Sergeeva et al ., ), we found that, in about 30% of the mouse TMN neurons identified by the expression of HDC, GABA‐responses are about halved by ZnCl 2 10 μM (Kletke et al ., ). In the present study, pyrazolopyridine CGS 20625, a two to six times more potent positive modulator of α1β2 than of α1β2γ receptors (Khom et al ., ), confirmed γ‐subunit‐deficiency of zinc‐sensitive TMN neurons [CGS 20625's EC 50 = 1.1 ± 0.1 μM ( n = 5, 28% of total cell number], which is significantly different ( P = 0.0055) from the zinc‐resistant cells (EC 50 = 3.4 ± 0.4 μM, n = 13, Supporting Information http://onlinelibrary.wiley.com/doi/10.1111/bph.12280/suppinfo).…”
Section: Resultsmentioning
confidence: 97%
“…Alternatively, receptors containing the γ1‐subunit (Puia et al ., ; Wafford et al ., ) or γ3‐subunit (Herb et al ., ) could mediate the response to zolpidem. No potentiation of GABA A R by zolpidem (1 or 10 μM) is observed in oocytes transfected with α1/2, β2/3, γ2 F77I ‐subunits (Buhr et al ., ; Ramerstorfer et al ., ; Kletke et al ., ), indicating that the ‘anaesthetics‐binding site’ present on β2 and β3 subunits is not involved. The modulatory potency and efficacy of diazepam and chlordiazepoxide was indifferent between WT and KI neurons in our study, whereas at recombinant α1β2γ2 F77I receptors the efficacy of diazepam is reduced (Ramerstorfer et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations